Social Policy and the Body
XXV, 219 p.
Keywords: The opening chapters suggest that transitions in welfare capitalism can be understood in terms of shifts in dominant 'corporeal' discourses. The body as a focus for power and resistance in differing welfare regimes is further explored in individual contributions on health and social care, bodily metaphors in social policy and the relationship between animal and human welfare. In highlighting the significance of the body in social policy, the book opens up a novel, and potentially rich, vein of academic enquiry.